We Who Were Slaves. Issue 4 (2nd October 2018) - Bogues, Anthony
Abstract : Working from the injunction of C. L. R. James about the requirement to understand the "new forms created in the context of slavery, " this essay argues that there is a political requirement for the study of the intellectual history and political thought of the African enslaved. The essay also notes that the Black enslaved body represented a distinct form of labor in which it produced commodities while itself being a "property in person." Such a historical process produced "thingfication, " and unique forms of domination and alternative frameworks of freedom.